2017
DOI: 10.1211/pj.2017.20202154
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with palliative care patients nearing the end of life, their families and carers

Abstract: Title:Communicating with palliative care patients, their loved ones and carers at the end of life Subtitle:Guidance and strategies to help pharmacists develop the skills for communicating with patients, their loved ones and carers at the end of life. Communicating with palliative care patients nearing the end of life, their families and carers Archer W., Latif A., Faull C. Subtitle:Pharmacists are becoming increasingly involved in palliative care and can be a source of important information and support for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Many of the communication challenges identified by this review are not unique to people living with ALS. For example, both this review and the palliative care literature identifies healthcare professionals' reluctance to address prognosis and end-of-life discussion avoidance (41, 115, 174, 175); difficulties identifying appropriate times for conversations about end of life (5, 115,164); and the changing needs of patients (163). ALS, however, presents additional communication challenges.…”
Section: Discussion Main Findings Of the Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the communication challenges identified by this review are not unique to people living with ALS. For example, both this review and the palliative care literature identifies healthcare professionals' reluctance to address prognosis and end-of-life discussion avoidance (41, 115, 174, 175); difficulties identifying appropriate times for conversations about end of life (5, 115,164); and the changing needs of patients (163). ALS, however, presents additional communication challenges.…”
Section: Discussion Main Findings Of the Scoping Reviewmentioning
confidence: 99%
“…The integral role of communication for end-of-life care is documented in the palliative care literature (5, 163,164). Yet, fewer than half of the selected articles focused explicitly on health communication.…”
Section: Discussion Main Findings Of the Scoping Reviewmentioning
confidence: 99%
“…Hope in the end‐of‐life context has been widely researched (Fanslow‐Brunjes, 2008; Mok et al, 2010). In a study of patients treated in hospices and palliative care centres, researchers showed that hope was considered one of the most important tools to enable the personalization and improvement of palliative care (Baczewska et al, 2019) and to integrate this knowledge into their practice health care professionals must understand the concept of hope in the end‐of‐life context (Archer et al, 2017; Chan et al, 2019; Chen et al, 2015; Daneault et al, 2016; McClement & Chochinov, 2008; Mok et al, 2010).…”
Section: Introductionmentioning
confidence: 99%